Dizziness and anxiety disorders in the elderly - O V Kotova (Терапевтический архив, 2016)
Perhaps each dizzy patient feels anxiety. Varying emotional disorders are particularly common in elderly patients with dizziness. The causes of the frequent concurrence of dizziness and mental disorders (anxiety and depression) are diverse. Amongst these there are two chief conditions: 1) vestibular vertigo may cause anxiety to a greater extent than many other symptoms; 2) anxiety and depression are themselves frequently manifested by the sensations resembling vestibular ones that patients are inclined to call dizziness. On the contrary, anxiety may appear in some cases as the sensations resembling dizziness. Besides the latter, the patient may present a lot of complaints, which serves as a manifestation of psychoautonomic syndrome (the basis for which is anxiety and depression). At the same time, the term «phobic postural instability» is proposed to describe psychogenic disorders, in which dizziness becomes virtually the only chief complaint. The treatment of dizziness and anxiety disorders in the elderly encompasses a few areas: vestibular rehabilitation, drug therapy, and psychotherapy. The paper describes the possibilities of using anvifen as a pathogenetically sound treatment in patients with anxiety disorders, as anvifen is a GABA-ergic medication.